2000
DOI: 10.1034/j.1600-0749.2000.130205.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Correction by RNA‐DNA Oligonucleotides

Abstract: of several hairs and DOPA staining of hair follicles in the An oligonucleotide composed of a contiguous stretch of RNA and DNA residues has been developed to facilitate the correctreated skin of albino mice. Such RDOs might hold a promise tion of single-base mutations of episomal and chromosomal as a therapeutic method for the treatment of skin diseases. targets in mammalian cells. The design of the oligonucleotide However, the frequency of gene correction varies among different cells, indicating that cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Our laboratory and others have shown that various forms of oligonucleotides, RNA-DNA oligonucleotide (RDO) and single-stranded oligodeoxynucleotide (ODN), are capable of chromosomal gene alterations in mammalian cells. 27 One of the major limitations of gene targeting is the low frequency of homologous recombination (10 À5 -10…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have shown that various forms of oligonucleotides, RNA-DNA oligonucleotide (RDO) and single-stranded oligodeoxynucleotide (ODN), are capable of chromosomal gene alterations in mammalian cells. 27 One of the major limitations of gene targeting is the low frequency of homologous recombination (10 À5 -10…”
Section: Discussionmentioning
confidence: 99%
“…These approaches use oligonucleotide technology related to triple-helix-forming oligonucleotide [1][2][3][4] and chimeric RNA-DNA oligonucleotide [5][6][7][8][9][10][11][12][13][14][15][16] for recognition and repair of the DNA sequence, and antisense oligonucleotides and ribozymes for editing RNA sequence. [17][18][19] Unlike gene replacement, where a therapeutic gene is transferred to the cell or affected organ, usually by virus-mediated gene transfer, this approach intends to produce predefined alterations in the DNA or RNA of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-DNA oligonucleotide was shown to cause a site-specific chromosomal correction or mutation in tissue culture cells and in vivo. [6][7][8][9][10][11][12][13][14][15][16] A permanent and stable gene correction by the RNA-DNA oligonucleotide was demonstrated by clonal analysis at the level of genomic sequence, protein and phenotypic change. 15 The RNA-DNA oligonucleotide might hold promise as a therapeutic method for the treatment of genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the chimeric RNA/DNA oligonucleotides (COs), a molecule consisting of RNA and DNA bases configured into a double-stranded, double hairpin conformation (1,2), has been used successfully to accomplish single-base exchange. These vectors have been used to repair point and frameshift mutations in mammalian cell culture (3)(4)(5)(6)(7)(8)(9), cell-free extracts (10)(11)(12) and animal models (13)(14)(15). In addition, gene repair using COs has been carried out successfully in plants ( [16][17][18] and plant cell-free extracts (19).…”
Section: Introductionmentioning
confidence: 99%